A literature review and meta‐analysis of outcomes in microsurgical reconstruction using vasopressors. Issue 3 (29th July 2018) - Knackstedt, Rebecca; Gatherwright, James; Gurunluoglu, Raffi
Abstract : Introduction: There is a hesitancy to utilize vasopressors in microsurgical reconstruction due to fear of vessel spasm and subsequent flap compromise. Although there are large literature reviews analyzing vasopressor usage in head and neck reconstruction, this has not been extrapolated to all regions of the body. The goal of this study was to perform a meta‐analysis examining vasopressor usage and risk of complications in microsurgical reconstruction for all recipient sites. Materials and Methods: A meta‐analysis was conducted for articles discussing the utilization of vasopressors in microsurgical reconstruction. The primary endpoint was total flap failure. Secondary endpoints were necessity for operative take‐back and hematoma requiring intervention. Odds ratios were calculated for each complication and for each study. Results: Four prospective and six retrospective studies were analyzed yielding 6321 patients and 7526 flaps. 67.4% (966/1433) of patients received vasopressors and 80.8% (6080/7526) of flaps received vasopressors. There were 100 failures in the vasopressor group (100/6080 = 15.9%) and 39 failures in the non‐vasopressor group (39/1456 = 26.8%) (O.R. 0.73; p = 0.12). There were 177 take‐backs in the vasopressor group (177/5916 = 29.9%) and 64 take‐backs in the non‐vasopressor group (64/1404 = 4.6%) (O.R. 0.65; p < 0.05). There were 73 hematomas in the vasopressor group (73/5099 = 14/3%) and 14 hematomas in the non‐vasopressor group (14/979 = 14.3%) (O.R. 1; p = 0.89). The odds ratio for total flaps failures in the breast and head/neck cohorts were 0.788 ( p = 0.76) and 1.2761 ( p = 0.77), respectively, with neither significantly increased in flaps receiving vasopressors. Conclusion: Our results suggest that vasopressor utilization does not directly result in increased complications. Flaps that received vasopressors had a statistically lower rate of take‐back and failure. Due to the paucity of data available for analysis and limited reporting relating flap characteristics to outcomes, prospective, well‐designed studies are necessary to verify the safety of vasopressor use in microsurgical reconstruction.